Nadir creatinine as a predictor of renal outcomes in PUVs: A systematic review and meta-analysis - Meneghesso, Davide; Bertazza Partigiani, Nicola; Spagnol, Rachele; Brazzale, Alessandra Rosalba; Morlacco, Alessandro; Vidal, Enrico (Frontiers in Pediatrics, 2023)
BACKGROUND Posterior urethral valves (PUV) represent the most severe obstructive uropathy in pediatric age, being responsible for chronic renal failure in up to 65% of cases and progression to end-stage kidney disease (ESKD) in about 8-21% of patients. Unfortunately, renal outcomes have poorly improved over time. A key point is to identify patients at risk, thus, several prenatal and postnatal prognostic factors have been analyzed to improve clinical outcomes. Postnatal nadir creatinine seems to accurately predict long-term renal prognosis, but there is a lack of definitive evidence to support this finding. OBJECTIVE We performed a systematic review with meta-analysis to analyze the predictive value of nadir creatinine on long-term renal function in infants with PUV. METHODS We conducted this systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed and Cochrane Library were systematically searched for studies published from January 2008 to June 2022. All the articles were checked independently by two reviewers in two steps. RESULTS A total of 24 articles were screened, and 13 were included for data extraction. Data from a total of 1731 patients with PUV were analyzed, with a mean follow up of 5.5 years; of these, on average 37.9% developed CKD and 13.6% ESKD. All the articles evaluated nadir creatinine as a predictor of CKD, most using a level of 1 mg/dl, with statistical significance at the 5% level. The relative risk of developing CKD in patients who present creatinine values higher than the nadir cut-off considered resulted 7.69 (95% CI: 2.35-25.17, I2=92.20%, p<0.001). CONCLUSIONS Nadir creatinine is the best prognostic factor of long term renal function in patients affected by PUV. A value above the cut-off of 1 mg/dl should be considered a significant predictor for the risk of CKD and ESKD. Further studies are needed to define different nadir creatinine cut-off for a better stratification of the different CKD stages and for the development of reliable scores which include the association of several different variables.